Delayed germination of Brassica parachinensis seeds by coumarin involves decreased GA4 production and a consequent reduction of ROS accumulation. Issue 3 (10th September 2021) - Chen, Bing-Xian; Peng, Yuan-Xuan; Yang, Xue-Qin; Liu, Jun
Abstract: The plant allelochemical coumarin effectively inhibits the germination of Brassica parachinensis ( B. parachinensis ) seeds. Quantification of endogenous phytohormones showed that contents of abscisic acid (ABA), ABA glucose ester, gibberellin A20 (GA20 ), GA3, GA15, GA24, GA9 and GA4 were higher in germinating seeds than in seedlings. Moreover, the presence of coumarin significantly reduced the content of bioactive GA4 which is thought to positively regulate seed germination. Histochemical staining and spectrophotometry of reactive oxygen species (ROS) revealed that exogenous GA3 and GA4+7 could effectively promote the production of endogenous ROS during germination and that the GA synthesis inhibitor paclobutrazol could effectively inhibit production of ROS. Coumarin significantly inhibited the accumulation of ROS, especially superoxide anion radical ( O_2^·- ). This inhibitory effect could be restored by the addition of exogenous GA3 and GA4+7 . Coumarin also inhibited the activity of the ROS-degrading enzymes such as superoxide dismutase, catalase and peroxidase as well as β-amylase in seeds and seedlings. Taken together, we propose a model for the regulation of seed germination in B. parachinensis by coumarin, Gas and ROS, in which coumarin may delay seed germination by reducing endogenous GA4, thus decreasing the accumulation of ROS.